Association between adjusted atherogenic index of plasma and major adverse cardiovascular events after percutaneous coronary intervention in patients with STEMI: a prospective observational study in China - Dong Wu; Xiaoying Wang; Ya Li; Xiaojuan Wang; Xiaowu Wang; Zhenfeng Yang; Zhen M A; Yongkai Ma; Guangli Li (BMJ Open)
Objectives The atherogenic index of plasma (AIP) has been reported as a biomarker for cardiovascular disease risks and clinical outcomes. However, few studies have investigated the relationship between the AIP and major adverse cardiovascular events (MACEs) after percutaneous coronary intervention (PCI) in patients with ST-segment elevation myocardial infarction (STEMI).Design Prospective observational study.Setting Data were collected from consecutive patients with STEMI who received PCI at Fuyang People’s Hospital from January 2023 to March 2024.Patients A total of 334 patients with STEMI who underwent PCI. The adjusted AIP (aAIP) was calculated using the following formula: aAIP=log ((triglyceride/high-density lipoprotein cholesterol × 100). The patient population was divided into four groups based on the aAIP quartiles.Primary and secondary outcome measures The primary outcome was MACEs, and the secondary outcomes included all-cause mortality, all-cause readmission and unplanned readmission as individual endpoints.Results Among 334 eligible patients, 68 (20.36%) experienced MACEs during a median follow-up of 8.70 months. After adjusting for confounders, continuous aAIP was positively correlated with MACEs in all three models. Patients in Q3 and Q4 had significantly higher MACE risks than Q1 (p<0.001 for each model), but no difference was observed between Q1 and Q2 (p>0.05 for each model). Compared with Q1, Q4 had significantly increased all-cause mortality risk (Model 2: HR=12.72, 95% CI 1.39 to 76.44 and Model 3: HR=16.18, 95% CI 1.66 to 117.50). All-cause readmission risk was also higher in Q3 and Q4 (Model 3: Q3: HR=2.242, 95% CI 1.043 to 4.818, p=0.039 and Q4: HR=5.378, 95% CI 2.557 to 11.314, p<0.001). Kaplan–Meier curves showed that higher aAIP was associated with increased risks of MACEs, all-cause readmission and unplanned readmission (all log-rank p<0.0001), but not all-cause mortality (log-rank p=0.1534). No significant interactions between subgroups and the aAIP were observed (p>0.05 for interaction).Conclusions Higher aAIP was significantly associated with increased risks of MACEs, all-cause readmission and unplanned readmission.